2020
DOI: 10.1177/0907568220923718
|View full text |Cite
|
Sign up to set email alerts
|

Friends through school and family: Refugee girls’ talk about friendship formation

Abstract: This article explores refugee girls’ talk about friendship formation. Friendship is a complex process and a subjective experience. The study participants stressed similarity and cultural affinity as important criteria of forming friendships. Those who attended schools with a mixture of students described their native peers as having different temperaments and interests. Relatives were referred to as being best friends who one could trust and confide in. This suggests the need for a broad conceptualisation of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…There may be different reasons for this: It may be due to living in the same areas, better possibilities of understanding each other's language, or a sense of social closeness due to shared experiences of migration and belonging to a minority as it has been demonstrated in other studies (cf. Bergnehr et al, 2020;Maegusuku-Hewett et al, 2007). Regardless of the possible reasons, this finding is nonetheless particularly informative, because it indicates that children with a migration background are evidently important gatekeepers who provide refugee children with access to social networks.…”
Section: Discussionmentioning
confidence: 85%
“…There may be different reasons for this: It may be due to living in the same areas, better possibilities of understanding each other's language, or a sense of social closeness due to shared experiences of migration and belonging to a minority as it has been demonstrated in other studies (cf. Bergnehr et al, 2020;Maegusuku-Hewett et al, 2007). Regardless of the possible reasons, this finding is nonetheless particularly informative, because it indicates that children with a migration background are evidently important gatekeepers who provide refugee children with access to social networks.…”
Section: Discussionmentioning
confidence: 85%
“…Alongside this parental support, Bergnehr et al. (2020) also found that for young Syrian and Iraqi refugee women in Sweden, relatives of a similar age were the most trusted and valued friends they could have. Having supportive relatives of a similar age who also attend school can be a powerful influencing factor for continuing their education.…”
Section: Resultsmentioning
confidence: 99%
“…Having friends at school, whether from the same migratory or ethnic background or not, has been said to provide ‘a sense of safety and contentedness’ for refugee girls (Bergnehr et al., 2020, p. 536). Indeed, the same was found to be true of adult refugee women in Türkiye: when they had a higher level of perceived social support, they were less likely to feel hopeless (Çankaya et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In migration research, it has also been commonplace to turn to children and youth and their perspectives to get insights into transnationalism and belongingness (see e.g. Bergnehr et al, 2020; Brocket, 2018; Katartzi, 2017, 2018; McDonnell, 2021). In research on transnationalism – and on being descendants of migrants in particular – I see a similar trend, and there has been a tendency to focus on the perspectives of youth in their late teens (Anthias, 2002; Toivanen, 2019; Ueda, 2002) and young adults in their twenties and thirties (Fouron & Glick‐Schiller, 2002; Kibriua, 2002; Runfors, 2016; Smith, 2002; Vickerman, 2002; Wolf, 2002), or both (Kasinitz et al, 2002; Levitt, 2002; Louie, 2002).…”
Section: Introductionmentioning
confidence: 99%